Competitive advantage model of the culinary industry in sukabumi city: technological capability, market orientation and business adaptation - Tera Lesmana; Endi Sarwoko; William Santoso (Jurnal Mantik, 2026)
The sustainability of competitive advantage in small culinary businesses depends not only on resources but also on their capacity to transform those resources into adaptive actions. This study examines business adaptation as a strategic mechanism linking technological capability and market orientation to competitive advantage in the culinary industry of Sukabumi City. Using a quantitative design, data were collected from 140 culinary business owners and analyzed with PLS-SEM. The findings reveal that market orientation significantly enhances competitive advantage both directly and indirectly through business adaptation. Adaptation emerges as the dominant mechanism translating market intelligence into operational and strategic adjustments. In contrast, technological capability does not significantly drive adaptation but directly strengthens competitive advantage through efficiency and service improvements. These results contribute to the dynamic capabilities perspective by demonstrating that adaptation is primarily activated by market-sensing capability rather than technological capability in micro and small enterprises. The study highlights that in contexts of limited digital maturity, competitive advantage is more strongly shaped by adaptive responsiveness than by technology adoption alone